Frailty and Sarcopenia - Onset, Development and Clinical Challenges 2017
DOI: 10.5772/intechopen.69639
|View full text |Cite
|
Sign up to set email alerts
|

From Sarcopenia to Frailty: The Pathophysiological Basis and Potential Target Molecules of Intervention

Abstract: Skeletal muscle is not only an endocrine organ but also one of core components of muscloskeletal system. Sarcopenia refers to a decline in the skeletal muscle mass and function. The former involves the size and number of changes in two types of myofibers, lower satellite cell density, and regeneration ability. The latter shows a loss of muscle strength. Frailty is a geriatric syndrome with multisystem impairment associated with increased vulnerability to stressors. Sarcopenia increases the risk of frailty and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 80 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…Hirani et al (41) also reported that the risk of frailty was significantly higher in the older adults with sarcopenic obesity than in those with non-sarcopenic normal weight, but it was not significantly different from those with non-sarcopenic obesity. It is well known that sarcopenia, defined as an abnormal loss of muscle mass and strength, is one of the major causes for an increase in the risk of frailty (42) . Falsarella et al (43) reported that frail older individuals had a lower muscle mass and higher percentage of body fat compared with non-frail older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Hirani et al (41) also reported that the risk of frailty was significantly higher in the older adults with sarcopenic obesity than in those with non-sarcopenic normal weight, but it was not significantly different from those with non-sarcopenic obesity. It is well known that sarcopenia, defined as an abnormal loss of muscle mass and strength, is one of the major causes for an increase in the risk of frailty (42) . Falsarella et al (43) reported that frail older individuals had a lower muscle mass and higher percentage of body fat compared with non-frail older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia, characterized by muscle dysfunction, slow gait velocity, and cognitive decline is also known to increase the risk of developing dementia [15]. Sarcopenia is potentially associated with the CF phenotype, as this condition increases the risks of both physical frailty and cognitive impairment [16]. Even though sarcopenia and physical frailty are often used interchangeably, these two phenotypes have different constructs, whereby sarcopenia indicates a progressive decline in the lean body mass or muscle mass that contributes to frailty development [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is potentially associated with the CF phenotype, as this condition increases the risks of both physical frailty and cognitive impairment [16]. Even though sarcopenia and physical frailty are often used interchangeably, these two phenotypes have different constructs, whereby sarcopenia indicates a progressive decline in the lean body mass or muscle mass that contributes to frailty development [16,17]. Hence, the link between physical and cognitive impairments as relevant predictors of dementia warrants the need for a multidimensional approach in the assessments and interventions of older adults with CF.…”
Section: Introductionmentioning
confidence: 99%
“… 9 ) Similar to frailty, sarcopenia predisposes older individuals to adverse consequences such as falls, disability, and mortality. 9 , 10 ) The reported prevalence of sarcopenia is 6%–22% in adults aged ≥65 years, depending on the care setting. 11 ) The plausible biological mechanisms linking sarcopenia and frailty include inflammatory responses, oxidative stress, and hormonal dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“… 11 ) The plausible biological mechanisms linking sarcopenia and frailty include inflammatory responses, oxidative stress, and hormonal dysregulation. 10 , 12 ) The complex intertwining relationship between sarcopenia and frailty has been likened to a “chicken and egg” situation. Sarcopenia is believed to be a fundamental component and possible antecedent of frailty, resulting in reduced muscle strength and gait speed, which characterize the physical manifestation of frailty.…”
Section: Introductionmentioning
confidence: 99%